HUBUNGAN ANTARA STATUS SOSIAL EKONOMI KELUARGA DENGAN KEMATIAN PERINATAL DI WILAYAH KERJA PUSKESMAS BAAMANG UNIT II SAMPIT KALIMANTAN TENGAH JANUARI-APRIL 2010 - Aisyan, Septiana Dwi Susanti; Jannah, Sitti Nur; Wardani, Yuniar (Universitas Ahmad Dahlan, 2011)
Background: Mortality is an indicator of perinatal health status of mothers and children in the general obstetric service. Puskesmas Baamang Unit II Sampit is one of the health service in the town of Sampit who are ready to provide health services to the community. Socioeconomic factors such as education, knowledge about health, nutrition and environmental health, beliefs, values, and poverty is an individual and family factors that affect mortality in the community. Low socioeconomic women who are unable to meet the daily needs because of economic constraints so that womens nutritional needs are not fulfilled, this will have an impact on pregnancy. The purpose of this study to determine the relationship between socioeconomic status families with perinatal mortality in the working area Puskesmas Baamang Unit II Sampit. Methods: This was an observational research with cross sectional design. Total sample of 81 people. Samples were taken with a total sampling technique, using primary and secondary. Results: This study showed that there was a relationship between the social economy of perinatal death with a family with a CC value = 0.636; X2 count> X2 table (12.271> 3.841) and Approx. .000 Sig is smaller than ? (0.05). Conclusion: There was a relationship between socioeconomic status families with perinatal mortality in the Puskesmas Baamang Unit II Sampit in Central Kalimantan. Key words: perinatal, lmortality, socioeconomic status, family.